2023
DOI: 10.2967/jnumed.122.265200
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tau PET to Stage Alzheimer Disease According to the Braak Staging Framework

Abstract: Amyloid-β plaques and neurofibrillary tangles (NFTs) are the 2 histopathologic hallmarks of Alzheimer disease (AD). On the basis of the pattern of NFT distribution in the brain, Braak and Braak proposed a histopathologic staging system for AD. Braak staging provides a compelling framework for staging and monitoring of NFT progression in vivo using PET imaging. Because AD staging remains based on clinical features, there is an unmet need to translate neuropathologic staging to a biologic clinical staging system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Alzheimer's Disease (AD) is characterized by the progressive accumulation of amyloid-beta (Aβ) plaques and neurofibrillary tangles (NFTs), with tau protein aggregates forming paired helical filaments (PHFs) and straight filaments (SFs) central to AD pathogenesis (1)(2)(3)(4)(5)(6). Positron emission tomography (PET) imaging with Aβ and tau ligands has enhanced diagnostic accuracy and understanding of AD progression (7). First-generation tau-PET ligands have enabled in vivo detection of tau tangles and have predictive capabilities for brain atrophy and cognitive decline in pre-symptomatic individuals (8)(9)(10)(11)(12)(13)(14).…”
Section: Mainmentioning
confidence: 99%
“…Alzheimer's Disease (AD) is characterized by the progressive accumulation of amyloid-beta (Aβ) plaques and neurofibrillary tangles (NFTs), with tau protein aggregates forming paired helical filaments (PHFs) and straight filaments (SFs) central to AD pathogenesis (1)(2)(3)(4)(5)(6). Positron emission tomography (PET) imaging with Aβ and tau ligands has enhanced diagnostic accuracy and understanding of AD progression (7). First-generation tau-PET ligands have enabled in vivo detection of tau tangles and have predictive capabilities for brain atrophy and cognitive decline in pre-symptomatic individuals (8)(9)(10)(11)(12)(13)(14).…”
Section: Mainmentioning
confidence: 99%
“…In AD, pathological tau appears early in the disease process in the entorhinal cortex and brainstem then progresses to synaptically connected brain regions in such a stereotypical fashion that the pattern of tau pathology is used to determine the stage of disease in post-mortem tissue 2 . This progressive tau spread has also been confirmed longitudinally in living people with AD through positron emission tomography with tracers that bind tau pathology [3][4][5] . Similarly, in primary tauopathies, tau pathology generally starts in restricted brain regions and spreads through the brain.…”
Section: Introductionmentioning
confidence: 75%
“…In this work, we sought to generate a Drosophila model of trans-synaptic tau spread. Despite testing multiple different experimental paradigms, we found that Drosophila are remarkably resistant to the trans-synaptic tau spread evidenced in human tauopathies and observed in mammalian model systems [3][4][5][6][7][8][9][10][11][12]16,17,21,22,55,56 . This important negative data demonstrates that, whilst exceptionally useful for a number of other studies in neurodegeneration, including modifiers of tau toxicity [57][58][59][60] , Drosophila are unlikely to be a suitable model for screening modifiers of trans-synaptic tau spread.…”
Section: Discussionmentioning
confidence: 93%
“…The T807 PET scans were assessed to determine the SUVRs for the inferior temporal lobe and Braak stage ROIs [Braak Stages I/II (transentorhinal), III/IV (limbic) and V/VI (neocortical)]. 17 , 28 We defined tau PET positivity based on a cut-off value of a SUVR ≥ 1.3 in any of the ROIs, according to a previous report. 29 …”
Section: Methodsmentioning
confidence: 99%